Peran Guru PPKn dalam Pembiasaan Nilai-Nilai Kearifan Lokal Kato Nan Ampek pada Kegiatan Projek Penguatan Profil Pelajar Pancasila (P5) - Destuliadi; Sudirman, Sudirman; Suhaili, Hidayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to describe the role of Civic Education (PPKn) teachers in habituating the implementation of local wisdom values of Kato Nan Ampek through the Project for Strengthening the Pancasila Student Profile (P5) at SMA Negeri 1 Situjuah Limo Nagari. This research employed a qualitative approach with a descriptive method. The findings indicate that the habituation of Kato Nan Ampek values in P5 activities faces several challenges. These include students’ low interest and awareness of local cultural values, the influence of social media, family environment, peer groups, and the surrounding community, which is less supportive of the preservation of local culture. To address these challenges, PPKn teachers play an active role through various efforts, such as providing advice and guidance to students, implementing the 5S habituation culture (smile, greeting, handshaking, addressing politely, and showing courtesy and respect), serving as role models in attitudes and behavior, giving consequences for actions that are not in accordance with the instilled values, and integrating Kato Nan Ampek values into P5 activities. Based on the findings, it can be concluded that PPKn teachers have an important and strategic role in instilling and habituating the local wisdom values of Kato Nan Ampek among students through P5 activities as an effort to develop character that is aligned with both local cultural values and the Pancasila Student Profile. Keywords: Local Wisdom, Kato Nan Ampek , Role of Civic Education Teachers